Knowledge Discovery, Knowlege Engineering and Knowledge Management First International Joint Conference, IC3K 2009, Funchal, Madeira, Portugal, October 6-8, 2009, Revised Selected Papers - Fred, Ana.; Dietz, Jan L. G.; Liu, Kecheng; Filipe, Joaquim; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2011)
This book constitutes the thoroughly refereed post-conference proceedings of the First International Joint Conference on Knowledge Discovery, Knowledge Engineering, and Knowledge Management, IC3K 2009, held in Funchal, Madeira, Portugal, in October 2009. This book includes revised and extended versions of a strict selection of the best papers presented at the conference; 27 revised full papers together with 3 invited lectures were carefully reviewed and selected from 369 submissions. According to the three covered conferences KDIR 2009, KEOD 2009, and KMIS 2009, the papers are organized in topical sections on on knowledge discovery and information retrieval, knowledge engineering and ontology development, and on knowledge management and information sharing
Keywords: Computer science; Computer Communication Networks; Software engineering; Data mining; Information storage and retrieval systems; Information systems; Computer Science; Information Systems Applications (incl.Internet).; Computer Communication Networks; Information Storage and Retrieval; Software Engineering; User Interfaces and Human Computer Interaction; Data Mining and Knowledge Discovery